Perancangan SPK Menentukan Kualitas Getah Karet Terbaik Dengan Metode AHP Di PT. Lonsum Bulukumba - Reski Amaliah; Joko Riyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
As time goes on, the development of technology is also increasing. People's lives are now dependent on technology, including companies in Indonesia, including PT. London Sumatra, located in Bulukumba Regency, South Sulawesi. The company is a company that focuses on rubber plantations. Rubber sap or commonly called latex is a thick solution obtained from tapping rubber rods. Latex is very useful for human life because it can be processed into tires, buckets, medical gloves and others. In determining the quality of PT. PP London Sumatra Indonesia Tbk. Bulukumba, in determining the quality of rubber sap, the company requires the use of information technology because in determining the quality of rubber the company only conducts research. It is less efficient because it takes a long time. There needs to be a system that can help workers to make time efficient. The application of the AHP method in determining the quality of rubber latex is very useful because it helps determine the priority of the many existing criteria.